Design and Ultrasound Assisted Synthesis of Novel 1, 3, 4‐Oxadiazole Drugs for Anti‐Cancer Activity. Issue 11 (17th March 2020) - Bhatt, Priyanka; Sen, Anik; Jha, Anjali
Abstract: An ultrasound assisted multi‐component synthesis of a series of 2‐( N ‐heterocycle) substituted 1, 3, 4‐oxadiazoles have been performed. A proper IR, UV, Mass and NMR spectral analysis supported the 12 synthesized novel compounds. Compound 5‐bromo‐1‐((4‐chlorophenyl)((5‐(4‐hydroxyphenyl)‐1, 3, 4‐oxadiazol‐2‐yl)amino)methyl) indoline‐2, 3‐dione (D8 ), displayed significant cytotoxicity against all the three human cancer cell lines studied in this article (breast cancer cell line MCF‐7, colorectal cancer cell line HT‐29 and liver cancer cell line Hep G2) using MTT assay. Further in silico target hunting using Chem Mapper led to the identification of two important cancer targets; EGFR and CDK2 kinases. Compound D8 was studied in detail using AutoDock and displayed high binding energies with the two proteins. Quantum chemical calculations of the designed compound D8 at the active site with specific amino acids for both the proteins showed stronger interactions at the active sites similar to the docking studies. Abstract : Twelve novel substituted 1, 3, 4‐oxidiazoles were synthesized with ultrasound assisted multicomponent method and characterised by IR, UV, Mass and NMR spectra. Cytotoxicity studies proved one of the synthesized compound 5‐bromo‐1‐((4‐chlorophenyl)((5‐(4‐hydroxyphenyl)‐1, 3, 4‐oxadiazol‐2‐yl)amino)methyl) indoline‐2, 3‐dione (D8), displayed significant cytotoxicity with human cancer cell lines. Molecular Docking and DFT studies also showed significant interaction of the D8 compound with two important cancer targets; EGFR and CDK2 kinases.